The Delta variant and the change of strategy on the public health chessboard - Pareja Cruz, Arturo (2021)
During the last few weeks, Peru has been a spectator of what has been happening in certain European countries and in the United States of America, where there has been a dramatic increase in COVID-19 cases and hospitalizations, mostly due to the delta variant of SARS CoV-2. The increase in severe clinical forms and hospitalizations has led to increased vaccination and greater interest in the process, particularly in cities with low immunization rates. Still, the United States lags behind the European Union in inoculations and many of its citizens remain reluctant to receive the vaccine.